Farmers’ perceptions of the impacts of Adansonia digitata L. leaves exploitation on its conservation and on livelihoods of local communities in Mali, West Africa - Sogodogo, Hadidjatou Nana; Sanogo, Kapoury; Sylvestre, DA Sie; Traoré, Souleymane S.; Ipou, Joseph (European Scientific Journal, ESJ, 2021)
Baobab tree species plays a significant role in the livelihoods of rural dwellers in the Sahel regions. This study was carried out to analyze farmer’s perceptions on the impacts of Adansonia digitata L. leaves exploitation on its conservation and on livelihoods of local communities. Data were collected by interviewing 120 farmers to elucidate the impacts of leaves exploitation as well as the contribution of the species on their livelihoods. Descriptive statistics and multiple regression analysis were used to analyze the data to identify the annual contribution and to determine the socio-demographic characteristics influencing farmer’s perception of baobab leaves harvesting techniques. The results show that non-timber forest products (NTFPs) are the second pillar to support the respondents after agriculture. Their contribution rate ranged between 4 and 7% in the study sites. The findings revealed that the annual income obtained per person from the exploitation of baobab leaves ranged from 33,714 FCFA (56.00 USD) to 52,857 FCFA (87.80 USD). Its contribution to annual household income varies between 2.51 and 5.4%. Two (used of machete and stick) out of the three (manual collection, used of machete and stick) methods used by farmers to harvest the baobab leaves, have negative impacts on baobab species conservation. Age, educational level, and gender are key factors influencing farmer’s perception of baobab leaves harvesting. In view of the importance of the baobab tree, it is imperative that the domestication and propagation of baobab trees should be supported through the adoption of improved agroforestry technologies. In addition, sustainable harvesting practices of baobab leaves is also recommended for the conservation of this species.